2013
DOI: 10.1016/j.jhazmat.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Scoping candidate minerals for stabilization of arsenic-bearing solid residuals

Abstract: Arsenic Crystallization Technology (ACT) is a potentially eco-friendly, effective technology for stabilization of arsenic-bearing solid residuals (ABSRs). The strategy is to convert ABSRs generated by water treatment facilities into minerals with a high arsenic capacity and long-term stability in mature, municipal solid waste landfills. Candidate minerals considered in this study include scorodite, arsenate hydroxyapatites, ferrous arsenates (symplesite-type minerals), tooeleite, and arsenated-schwertmannite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 45 publications
(47 reference statements)
1
15
0
Order By: Relevance
“… 39 used goethite, lepidocrocite and green rust to remediate arsenic and found that green rust was also transformed to parasymplesite in a reducing environment, resulting in significant attenuation of arsenic. Parasymplesite was previously demonstrated to be a good candidate for treating arsenic-bearing solid residuals, and it also passed the toxicity characteristic leaching procedure (arsenic leaching < 5 mg/L) 40 . The removal of As(V) under anoxic conditions by CSF was thus established as a promising approach for achieving highly efficient arsenic removal and forming stable products at the same time.…”
Section: Resultsmentioning
confidence: 99%
“… 39 used goethite, lepidocrocite and green rust to remediate arsenic and found that green rust was also transformed to parasymplesite in a reducing environment, resulting in significant attenuation of arsenic. Parasymplesite was previously demonstrated to be a good candidate for treating arsenic-bearing solid residuals, and it also passed the toxicity characteristic leaching procedure (arsenic leaching < 5 mg/L) 40 . The removal of As(V) under anoxic conditions by CSF was thus established as a promising approach for achieving highly efficient arsenic removal and forming stable products at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the As(V) incorporated into schwertmannite may retard or significantly inhibit the Fe 2+ -catalyzed transformation of schwertmannite to goethite. It has also been reported that the presence of As(V) stabilizes schwertmannite and inhibits or significantly retards Fe(II)-catalyzed transformation to goethite (Burton et al, 2010;Raghav et al, 2013).…”
Section: Effect Of Fe 2+ On Sch-as Stabilitymentioning
confidence: 99%
“…7b), indicating that Sch-As products here may be stable and that no solid transformation occurs. As(V) incorporated into schwertmannite may retard or significantly inhibit the transformation into more stable iron oxides (Fukushi et al, 2003;Burton et al, 2010Burton et al, , 2009Raghav et al, 2013;Regenspurg and Peiffer, 2005).…”
Section: Effect Of Time On Sch-as Stabilitymentioning
confidence: 99%
“…The crystallization technology promotes the earth-mimetic mineral precipitation phenomena, compounds with a high capacity of crystallizing the toxic elements with long-term stability. Scorodite (FeAsO 4 •2H 2 O), tooeleite (Fe 6 (AsO 3 ) 4 SO 4 (OH) 4 •4H 2 O), and hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) are examples of minerals that contain high quantities of toxic elements [25]. Scorodite is a very attractive compound for stabilizing arsenic due to its low solubility, high removal efficiency, low iron demand, and low volumes of waste material produced [26][27][28].…”
Section: Weak Acid Treatmentmentioning
confidence: 99%
“…Tooeleite is an attractive mineral for wastewater treatment because of its high arsenic load (20-25% wt/wt) and natural stabilization during long periods [17,29]. The hydroxyapatites are a series of minerals that have been studied for the immobilization of lead, cadmium, nickel, copper, mercury, and arsenic [25].…”
Section: Weak Acid Treatmentmentioning
confidence: 99%